2021
DOI: 10.1080/13603116.2021.1937344
|View full text |Cite
|
Sign up to set email alerts
|

Increasing faculty’s competence in digital accessibility for inclusive education: a systematic literature review

Abstract: The use of information and communications technology (ICT) in higher education institutions has increased in the past 20 years. While ICT has brought many benefits to students and faculty, research shows that it also creates barriers and challenges for students with disabilities due to the inaccessibility of digital tools and learning materials. Faculty members play an important role in inclusive higher education. Previous studies have emphasised the need to train faculty about digital accessibility to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 24 publications
0
39
0
3
Order By: Relevance
“…There has also been an effort to address the needs of disabled students within higher education more broadly, as part of a desire to make various educational policies and practices more inclusive to such students. However, expecting faculty to acquire the skills needed to provide inclusive educational experiences, such as those needed to remediate OER for accessibility, presents a major challenge (Bong & Chen, 2021). Several studies have found that faculty report various barriers to using OER, including technology (Belikov & Bodily, 2016;Hong Xu, 2018;Iniesto et al, 2021;Jung et al, 2017;Martin & Kimmons, 2020;Taylor & Taylor, 2018;Zeichner, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been an effort to address the needs of disabled students within higher education more broadly, as part of a desire to make various educational policies and practices more inclusive to such students. However, expecting faculty to acquire the skills needed to provide inclusive educational experiences, such as those needed to remediate OER for accessibility, presents a major challenge (Bong & Chen, 2021). Several studies have found that faculty report various barriers to using OER, including technology (Belikov & Bodily, 2016;Hong Xu, 2018;Iniesto et al, 2021;Jung et al, 2017;Martin & Kimmons, 2020;Taylor & Taylor, 2018;Zeichner, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some specifically focus on ensuring the accessibility of OER. Most recommendations center around educating or training and heavily supporting potential faculty authors and adopters, but other strategies have also been put forward (Bong & Chen, 2021). Two specific examples include the creation (and subsequent assessment) of a learning analytics tool (Avila et al., 2020) and the development of a new workflow for library publishing, or other campus publishing units, that place accessibility at the forefront (Thomas et al, 2021).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The use of information and communication technologies (ICT) in the education process has escalated in recent years and has gained significance worldwide, especially after the COVID-19 pandemic. Many educational institutions and learners benefit from digital technologies such as learning management systems (LMS) and digital learning tools that allow teachers and students to enroll in online classes [1]. The introduction of digital technologies in the educational context provides the opportunity to personalize the presentation of information, select the pace of learning individually, assess competencies objectively, and increase the level of methodological support in the educational process [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies point out the role of digital transformation by involving digital technologies in the education process and providing inclusive digital learning environments. The studies stress that providing access to inclusive education can help integrate people with different social, cultural, economic, physical, and mental differences into the active social, economic, and cultural life of society [1,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…University education has not remained oblivious to the digital revolution (Zimmermann et al, 2019), and has implemented various actions to adapt its teaching system to the current reality (Campbell et al, 2020). In addition, the situation produced by the COVID-19 health emergency has further highlighted the need to use technologies and to know how they influence learning processes (Bong & Chen, 2021). In the specific case of Spain, the Universitic 2020 report highlights the provision of computer equipment to Spanish universities, the creation of IT services to support teaching, , t. 146, Nr.…”
Section: Introductionmentioning
confidence: 99%